Access to research inputs: Open science versus the entrepreneurial university - Dirk Czarnitzki; Christoph Grimpe; Maikel Pellens (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
The viability of modern open science norms and practices depend on public disclosure of new knowledge, methods, and materials. However, increasing industry funding of research can restrict the dissemination of results and materials. We show, through a survey sample of 837 German scientists in life sciences, natural sciences, engineering, and social sciences, that scientists who receive industry funding are twice as likely to deny requests for research inputs as those who do not. Receiving external funding in general does not affect denying others access. Scientists who receive external funding of any kind are, however, 50% more likely to be denied access to research materials by others, but this is not affected by being funded specifically by industry.
urn:nbn:de:bsz:180-madoc-365828
Keywords: O31; O32; L33; 330; open science; research funding; industry sponsorship; research inputs